Харчовий ринок України на передодні вступу до СОТ - Березянко, Тамара Володимирівна (My University, 2005)
Статтю присвячено проблемам на першочерговим наслідкам вступу до СОТ для харчової промисловості. Розглянуто думки аналітиків національних та західних, наведено оцінки та перестороги щодо штучного прискорення вступу. The article deals with the problems and priorities of the expected consequences for the food industry as a result of WTO accession. Having considered the views of leading national and foreign experts, given the positive and negative assessments of the expected results for the artificial acceleration of the entry fields.
Keywords: СОТ; харчова промисловість; конкурентна політика; WTO; food industry; competition policy; кафедра економіки праці та менеджменту